SOME METHODOLOGICAL ASPECTS OF TRAINING IT PROFESSIONALS - Leshchuk, С.О. (Journal of Information Technologies in Education (ITE), 2017)
The important task of higher educational establishments is preparation of competitive professional, man that easily feels in market conditions and informative society. Next to possessing of informatively-communication technologies necessary abilities to study in a group, skills of prosecution of general projects. The aim of the article is to show possibility of organization of educational activity of students with maintenance and form works that is required by modern industry of information technologies. An author is describe separate steps preparations of future specialists, that is required by a IT-sphere; specialists that own a modern tool are understood by modern approaches in programming; able to work in a command above a general project and to arrive at a result. The basic ideas of the object-oriented programming are considered, methodology of management projects for the flexible Scrum and possibilities of the use of control system by versions software development, as a powerful instrument that gives an opportunity simultaneously, swimmingly to each other, to conduct the prosecution of group projects. Description comes true on the basis of realization of the special course for specialists on the informatics of specialities «Applied mathematics», «Informatics» of physics-mathematics faculty (Ternopil Volodymyr Hnatyuk National Pedagogical University). The table of contents of material is extended also by an acquaintance with the architectural template of MVC and generalization of abilities of work with a programmatic tool, by a necessity for creation of web-projects. The practical achievement of educational activity of students is development of social web-project with the aim of increase of level of culture of society and benevolent atmosphere of city.